Catacombs : a tale of the Barque cats - McCaffrey, Anne (Ballantine Books, 2011)
The barque cats, mistaken for a public health hazard, flee Earth for the feline-dominated planet, Mau, with the help of Pshaw-Ra, a mysterious cat with his own spaceship. Oddly, no one--including the humans--is bothered that he plans to take over the universe on behalf of felinekind.